Pemanfaatan Harta Kekayaan yang Diperoleh Secara Ilegal: Tinjauan Hukum Islam - Sabaruddin; Kurniati; Mustafa, Zulhas' ari; Wahyudi, Feri Eko; Kulle, Haris; Firmansyah (Al-Amwal : Journal of Islamic Economic Law, 2025)
Purpose  – Wealth is an essential and fundamental aspect of human life. It not only plays an important role in sustaining life, but also serves as a means to achieve prosperity and happiness, both in this world and in the hereafter. Although the Qur'an explicitly prohibits the acquisition of wealth through unlawful means, violations of this provision still occur frequently. In fact, seeking halal livelihood is an obligation for every Muslim. Therefore, it is important to conduct in-depth research on sources of income that are haram, so that they can be avoided, while also examining the perspective of Islamic economics in managing haram wealth for those who are already involved and wish to purify it. Method – This study uses a normative-descriptive method with a sociological-legal approach. Data collection was conducted through literature study by examining various relevant sources, such as fiqh books, scientific journals, fatwas from scholars, and previous research results. Result – The results of the research show in Islamic jurisprudence, unlawful wealth refers to assets acquired through forbidden means, such as gambling, oppression, usury, theft, corruption, or the sale of prohibited goods, as explicitly forbidden by the Quran and Hadith. The management of illicit wealth in the context of Islamic economics must be based on the principles of justice, purification, and divine trust (istikhlāf). Scholars such as al-Ghazālī, Ibn Qudāmah, Wahbah al-Zuḥaylī, and Yūsuf al-Qaraḍāwī agree that wealth obtained unlawfully must be returned to its rightful owner. If the owner is unknown, then the wealth must be allocated for the public good. Therefore, individuals, groups, and governments are obliged to manage unlawful wealth in a manner that brings public benefit and is in accordance with divine justice. Implication – As a practical implication these Islamic legal principles is that Muslims are strictly obligated to cleanse their finances of unlawfully acquired wealth, primarily by returning it to its rightful owner or, failing that, by dedicating it to public good, preferably, the government should establish an institution to facilitate this.